Salvia hispanica L. (chia) seed improves skeletal muscle lipotoxicity and insulin sensitivity in rats fed a sucrose-rich diet by modulating intramuscular lipid metabolism - Ferreira Cordoneda, Maria del Rosario (2020)
This study investigates the possible mechanisms involved in the beneficial effect of chia seed on skeletal muscle lipotoxicity and insulin resistance in rats fed a sucrose-rich diet (SRD). Results showed that chia seed reduced the increased lipid content in the skeletal muscle of SRD-fed rats. This was accompanied by an increase of muscle-type carnitine palmitoyltransferase 1 enzyme activity, peroxisome proliferator-activated receptors (PPARα, PPARγ) and phosphorylated AMP activated protein kinase protein levels. Moreover, the precursor and mature forms of sterol regulatory element-binding protein-1 and lipogenic enzyme activities were decreased. Fatty acid translocase FAT/CD 36 and n-3/n-6 fatty acids ratio of membrane phospholipids were increased. This work shows that an increase in the key factors levels associated with muscle oxidative capacity and a reduction in the lipogenic pathway would be some mechanisms involved in the beneficial effects of chia seed on skeletal muscle lipotoxicity in insulin resistant SRD-fed rats.